Theoretical Framework for Creep Effect Analysis of Axially Loaded Short CFST Columns under High Stress Levels. (21st May 2020) - Li, Shiwei; Yang, Yongqing; Wen, Wangqing; Yan, Aiguo
Abstract : Due to its excellent mechanical performances, axially loaded concrete-filled steel circular tube (CFST) columns have been widely used in structural engineering. As an important long-term behaviour of CFST structures, the creep has an obvious nonlinear property under high stress levels, which makes the influence of creep more complicated. In this study, to analyze the impacts of nonlinear creep effect on the behaviour of axially loaded short CFST columns, a complete theoretical framework for coupling analysis of 3D creep effect and material nonlinearity was presented. First, the concrete damaged plasticity model with a uniform constraint (UCCDP) was established to simulate the plasticity and damage evolution of a concrete core. Next, based on the UCCDP, a method of 3D nonlinear creep analysis and a corresponding numerical analysis method were established and implemented in the ABAQUS secondary platform. Finally, by comparing the predicted results with the experimental results, it was observed that the method proposed to predict the creep of axially loaded short CFST columns had satisfactory accuracy.